2006
DOI: 10.1177/107602960601200205
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Behavior of Endothelial and Coagulation Markers in Eisenmenger Syndrome

Abstract: The long-term behavior of endothelial markers was studied in patients with Eisenmenger syndrome who were subjected to conventional therapy (no vasodilators) and observed for 18 months. Biochemical markers were analyzed comparatively in patients with class II or III symptoms (group 1, n=10) and patients with class IV symptoms (group 2, n=7). Plasma von Willebrand factor antigen (vWF: Ag), thrombomodulin, tissue-type plasminogen activator (t-PA) and its inhibitor (PAI-1), and D-dimer were determined by immunoenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(40 reference statements)
2
6
0
Order By: Relevance
“…The elevated vWF levels in PAH‐CSPS denote an activated endothelium in these individuals as described by others 3,4,15,16 . Furthermore, it has previously been reported that PAH‐CSPS patients are characterized by increased plasma levels of tissue‐type plasminogen activator and decreased levels of thrombomodulin, suggesting an inflammatory and procoagulant state of the endothelium in these patients.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The elevated vWF levels in PAH‐CSPS denote an activated endothelium in these individuals as described by others 3,4,15,16 . Furthermore, it has previously been reported that PAH‐CSPS patients are characterized by increased plasma levels of tissue‐type plasminogen activator and decreased levels of thrombomodulin, suggesting an inflammatory and procoagulant state of the endothelium in these patients.…”
Section: Discussionsupporting
confidence: 59%
“…The elevated vWF levels in PAH-CSPS denote an activated endothelium in these individuals as described by others. 3,4,15,16 Furthermore, it has previously been reported that PAH-CSPS patients are characterized by increased plasma levels of tissuetype plasminogen activator and decreased levels of thrombomodulin, suggesting an inflammatory and procoagulant state of the endothelium in these patients. In the present study, we extend these findings by showing that the elevated levels of vWF in patients with PAH-CSPS are accompanied by a marked rise in plasma levels of sCD40L, primarily reflecting platelet-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, patients born in places at high altitudes have a higher prevalence of PDAs and develop severe pulmonary hypertension early on in the course of the natural history. Extensive local research in this field has provided some interesting observations about endothelial and coagulation abnormalities and vascular remodelling 899091929394959697. The benefits of haemodilution in these patients can be marked 98.…”
Section: Outcomes After Medical Surgical or Interventional Treatmentmentioning
confidence: 99%